Interleukin‐4 Gene Transfection and Spheroid Formation Potentiate Therapeutic Efficacy of Mesenchymal Stem Cells for Osteoarthritis. Issue 5 (24th January 2020) - Song, Seuk Young; Hong, Jihye; Go, Seukhyeong; Lim, Songhyun; Sohn, Hee Su; Kang, Mikyung; Jung, Gun‐Jae; Yoon, Jeong‐Kee; Kang, Mi Lan; Im, Gun‐il; Kim, Byung‐Soo
Abstract: Osteoarthritis (OA) is a painful intractable disease that significantly affects patients' quality of life. However, current therapies, such as pain killers and joint replacement surgery, do not lead to cartilage protection. Mesenchymal stem cells (MSCs) have been proposed as an alternative strategy for OA therapy because MSCs can secrete chondroprotective and anti‐inflammatory factors. However, interleukin‐4 (IL‐4), a potent anti‐inflammatory cytokine, is barely produced by MSCs, and MSC therapy suffers from rapid MSC death following intra‐articular implantation. MSCs in spheroids survive better than naïve MSCs in vitro and in vivo. IL‐4‐transfected MSCs in spheroids (IL‐4 MSC spheroid) show increased chondroprotective and anti‐inflammatory effects in an OA chondrocyte model in vitro. Following intra‐articular implantation in OA rats, IL‐4 MSC spheroids show better cartilage protection and pain relief than naïve MSCs. Thus, IL‐4 MSC spheroid may potentiate the therapeutic efficacy of MSCs for OA. Abstract : Mesenchymal stem cell (MSC) therapy is a rising strategy for treating osteoarthritis (OA). However, MSCs undergo rapid death after implantation and anti‐inflammatory cytokines such as interleukin‐4 (IL‐4) is barely produced in MSCs. Here, IL‐4 gene‐transfected MSCs in spheroids may potentiate the therapeutic efficacy of MSCs for OA by alteration the microenvironment in arthritic joint and prolonging survival of implanted MSCs.